THE QUEST FOR EQUITABLE JUSTICE: A CRITICAL REVIEW OF THE ADMINISTRATION OF CRIMINAL JUSTICE ACT IN NIGERIA - Adekunle, Victor Oluwaseun; Okoro, Grace Ifeoma (Ayden International Journal of Law, Political Science, and Administration, 2024)
In Nigeria, ensuring equitable access to justice remains a pivotal challenge, impeded by systemic issues such as protracted delays, exorbitant litigation costs, complex legal frameworks, and widespread corruption. These barriers significantly hinder the enforcement of human and contractual rights, thereby undermining the protection of human rights and the rule of law. This article delves into the importance of unhindered access to the judicial system in Nigeria, highlighting its role in the effective enforcement of rights. It examines the potential of integrating innovative judicial approaches, such as restorative justice and victim-offender mediation, which promise mutual benefits for the state, offenders, and crime victims alike. These approaches, coupled with effective case flow management, case front-loading, pretrial conferences, and alternative dispute resolution (ADR) mechanisms, are proposed as strategic solutions to alleviate judicial delays and reduce litigation costs. By exploring these methodologies, the article suggests a pathway towards a more responsive and costeffective justice system in Nigeria, fostering a more just societ